2021
DOI: 10.3233/wor-203392
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of religiosity and hope for the effect of self-stigma on psychological well-being among COVID-19 patients

Abstract: BACKGROUND: Over the past few months, there has been a significant increase in mortality and morbidity due to Coronavirus disease (COVID-19). Less attention has been paid to stigmatism, psychological well-being, hope, and religiosity, and how these may impact a patient’s recovery. OBJECTIVES: This study aimed to detect the difference in religiosity, hope, self-stigma, and psychological well-being (PWB) due to demographic variables (age, education level, social status, and level of income). Additionally, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…In the same line, (Al Eid et al, 2021 ) showed that religiosity had a direct positive effect on the psychological well-being of COVID-19 patients, suggesting that the greater the individual’s religiosity, the greater his psychological well-being.…”
Section: Resultsmentioning
confidence: 88%
“…In the same line, (Al Eid et al, 2021 ) showed that religiosity had a direct positive effect on the psychological well-being of COVID-19 patients, suggesting that the greater the individual’s religiosity, the greater his psychological well-being.…”
Section: Resultsmentioning
confidence: 88%
“…Stigma negatively affects (suspected) patients' and survivors' mental health because the stigmatized perceive themselves as alienated, isolated, and belonging to a devalued group and perceive stigma as unfair. Indeed, empirical findings generally show that stigma harms (suspected) patients' and survivors' mental health and leads to issues like depression (Liu D. et al, 2020 ; Xin et al, 2020 ; Grover et al, 2021 ; Harjana et al, 2021 ; Jayakody et al, 2021 ; Kang et al, 2021 ; Yuan et al, 2021 ), anxiety (Liu D. et al, 2020 ; Atinga et al, 2021 ; Gopichandran and Subramaniam, 2021 ; Grover et al, 2021 ; Harjana et al, 2021 ; Jayakody et al, 2021 ; Kang et al, 2021 ), mental health disorders (Adom et al, 2021 ; Miconi et al, 2021a ; Paleari et al, 2021 ), lower well-being (Ransing et al, 2020 ; Al Eid et al, 2021 ; Paleari et al, 2021 ; Sahoo and Patel, 2021 ), PTSD (Liu D. et al, 2020 ; Grover et al, 2021 ; Kang et al, 2021 ; Mahmoudi et al, 2021 ; Poyraz et al, 2021 ; Gan et al, 2022 ), and even self-harm or suicide (Ransing et al, 2020 ; Xin et al, 2020 ; Sahoo and Patel, 2021 ). For example, in a large sample involving more than 20,000 Chinese students, one study found that perceived discrimination due to COVID-19 is positively related to self-harm or suicidal ideation (Xin et al, 2020 ).…”
Section: Outcomes Of Stigma Toward (Suspected) Patients and Survivorsmentioning
confidence: 99%
“…The role of spirituality in coping with stressful situations is highlighted here again, since positive religious coping can lead to thinking positively about adverse events and help reduce depressive and/or stressful symptoms ( Mahamid & Bdier, 2021 ). Furthermore, hope could act as a buffer against the anxiety and stress of the virus pandemic caused by the closure of COVID or social distancing ( Al Eid et al, 2021 ). Since such limitations were imposed, religious support suffered important consequences and the religious rituals and needs during hospitalisation were impaired.…”
Section: Discussionmentioning
confidence: 99%